Metal-free synthesis of biarenes via photoextrusion in di(tri)aryl phosphates - Qrareya, Hisham; Meazza, Lorenzo; Protti, Stefano; Fagnoni, Maurizio (Beilstein Journal of Organic Chemistry, 2020)
A metal-free route for the synthesis of biarenes has been developed. The approach is based on the photoextrusion of a phosphate moiety occurring upon irradiation of biaryl- and triaryl phosphates. The reaction involves an exciplex as the intermediate and it is especially suitable for the preparation of electron-rich biarenes.
Keywords: aryl phosphates; biarenes; metal-free synthesis; photochemistry; photoextrusion

(untitled) - Hajduk, P. J.; Bures, M.; Praestgaard, J.; Fesik, S. W. (J. Med. Chem., 2000)

(untitled) - Horton, D. A.; Bourne, G. T.; Smythe, M. L. (Chem. Rev., 2003)

(untitled) - Klekota, J.; Roth, F. P. (Bioinformatics, 2008)

(untitled) - Goa, K. L.; Wagstaff, A. J. (Drugs, 1996)

(untitled) - McElroy, W. T.; DeShong, P. (Tetrahedron, 2006)

(untitled) - Torres, J. C.; Pinto, A. C.; Garden, S. J. (Tetrahedron, 2004)

(untitled) - Bringmann, G.; Price Mortimer, A. J.; Keller, P. A.; Gresser, M. J.; Garner, J.; Breuning, M. (Angew. Chem., Int. Ed., 2005)

(untitled) - Noyori, R.; Takaya, H. (Acc. Chem. Res., 1990)

(untitled) - Wallace, T. W. (Org. Biomol. Chem., 2006)

(untitled) - Berthod, M.; Mignani, G.; Woodward, G.; Lemaire, M. (Chem. Rev., 2005)

(untitled) - Vasconcelos, S. N. S.; Reis, J. S.; de Oliveira, I. M.; Balfour, M. N.; Stefani, H. A. (Tetrahedron, 2019)

(untitled) - Nguyen, T. T. (Org. Biomol. Chem., 2019)

(untitled) - Felpin, F.-X.; Sengupta, S. (Chem. Soc. Rev., 2019)

(untitled) - Fanta, P. E. (Chem. Rev., 1946)

(untitled) - Sambiagio, C.; Marsden, S. P.; Blacker, A. J.; McGowan, P. C. (Chem. Soc. Rev., 2014)

(untitled) - Amaya, T.; Jin, Y.; Tobisu, M. (Tetrahedron Lett., 2019)

Metal-Catalyzed Cross-Coupling Reactions - de Meijere, A.; Diederich, F. (Wiley-VCH, 2004)

Synthesis of biaryls - Cepanec, I. (Elsevier, 2004)

(untitled) - Hussain, I.; Singh, T. (Adv. Synth. Catal., 2014)

(untitled) - García-López, J.-A.; Greaney, M. F. (Chem. Soc. Rev., 2016)

(untitled) - Hassan, J.; Sévignon, M.; Gozzi, C.; Schulz, E.; Lemaire, M. (Chem. Rev., 2002)

(untitled) - Nicolaou, K. C.; Bulger, P. G.; Sarlah, D. (Angew. Chem., Int. Ed., 2005)

(untitled) - Hussain, I.; Capricho, J.; Yawer, M. A. (Adv. Synth. Catal., 2016)

(untitled) - Sun, C.-L.; Shi, Z.-J. (Chem. Rev., 2014)

(untitled) - Sun, C.-L.; Li, H.; Yu, D.-G.; Yu, M.; Zhou, X.; Lu, X.-Y.; Huang, K.; Zheng, S.-F.; Li, B.-J.; Shi, Z.-J. (Nat. Chem., 2010)

(untitled) - Sawama, Y.; Asai, S.; Kawajiri, T.; Monguchi, Y.; Sajiki, H. (Chem. – Eur. J., 2015)

(untitled) - Guo, L.; Liu, F.; Wang, L.; Yuan, H.; Feng, L.; Kürti, L.; Gao, H. (Org. Lett., 2019)

(untitled) - Dichiarante, V.; Protti, S.; Fagnoni, M. (J. Photochem. Photobiol., A, 2017)

(untitled) - Lazzaroni, S.; Ravelli, D.; Protti, S.; Fagnoni, M.; Albini, A. (C. R. Chim., 2017)

(untitled) - Hofmann, J.; Heinrich, M. R. (Tetrahedron Lett., 2016)

(untitled) - Ghosh, I.; Marzo, L.; Das, A.; Shaikh, R.; König, B. (Acc. Chem. Res., 2016)

(untitled) - Milanesi, S.; Fagnoni, M.; Albini, A. (Chem. Commun., 2003)

(untitled) - Barragan, E.; Poyil, A. N.; Yang, C.-H.; Wang, H.; Bugarin, A. (Org. Chem. Front., 2019)

(untitled) - Fagnoni, M.; Mella, M.; Albini, A. (Org. Lett., 1999)

(untitled) - Dichiarante, V.; Fagnoni, M.; Albini, A. (Angew. Chem., Int. Ed., 2007)

(untitled) - De Carolis, M.; Protti, S.; Fagnoni, M.; Albini, A. (Angew. Chem., Int. Ed., 2005)

(untitled) - Qrareya, H.; Protti, S.; Fagnoni, M. (J. Org. Chem., 2014)

(untitled) - Crespi, S.; Protti, S.; Fagnoni, M. (J. Org. Chem., 2016)

(untitled) - da Silva Júnior, P. E.; Amin, H. I. M.; Nauth, A. M.; da Silva Emery, F.; Protti, S.; Opatz, T. (ChemPhotoChem, 2018)

(untitled) - Qiu, D.; Lian, C.; Mao, J.; Fagnoni, M.; Protti, S. (J. Org. Chem., 2020)

(untitled) - Motherwell, W. B.; Pennell, A. M. K. (J. Chem. Soc., Chem. Commun., 1991)

(untitled) - da Mata, M. L. E. N.; Motherwell, W. B.; Ujjainwalla, F. (Tetrahedron Lett., 1997)

(untitled) - da Mata, M. L. E. N.; Motherwell, W. B.; Ujjainwalla, F. (Tetrahedron Lett., 1997)

(untitled) - Holden, C. M.; Sohel, S. M. A.; Greaney, M. F. (Angew. Chem., Int. Ed., 2016)

(untitled) - Rasheed, O. K.; Hardcastle, I. R.; Raftery, J.; Quayle, P. (Org. Biomol. Chem., 2015)

(untitled) - Yanagi, T.; Nogi, K.; Yorimitsu, H. (Chem. – Eur. J., 2020)

(untitled) - Yanagi, T.; Otsuka, S.; Kasuga, Y.; Fujimoto, K.; Murakami, K.; Nogi, K.; Yorimitsu, H.; Osuka, A. (J. Am. Chem. Soc., 2016)

(untitled) - Morioka, T.; Nishizawa, A.; Furukawa, T.; Tobisu, M.; Chatani, N. (J. Am. Chem. Soc., 2017)

(untitled) - Somerville, R. J.; Martin, R. (Angew. Chem., Int. Ed., 2017)

(untitled) - Takahashi, F.; Nogi, K.; Yorimitsu, H. (Org. Lett., 2018)

(untitled) - Kloss, F.; Neuwirth, T.; Haensch, V. G.; Hertweck, C. (Angew. Chem., Int. Ed., 2018)

(untitled) - Okamoto, Y.; Nakamura, M.; And, M. S.; Takamuku, S. (Photochem. Photobiol., 1992)

(untitled) - Shi, M.; Okamoto, Y.; Takamuku, S. (Tetrahedron Lett., 1991)

(untitled) - Nakamura, M.; Sawasaki, K.; Okamoto, Y.; Takamuku, S. (J. Chem. Soc., Perkin Trans. 1, 1994)

(untitled) - Nakamura, M.; Shi, M.; Okamoto, Y.; Takamuku, S. (J. Photochem. Photobiol., A, 1995)

(untitled) - Okamoto, Y.; Tatsuno, T.; Takamuku, S. (Phosphorus, Sulfur Silicon Relat. Elem., 1996)

(untitled) - Finnegan, R. A.; Matson, J. A. (J. Am. Chem. Soc., 1972)

(untitled) - Shi, M.; Yamamoto, K.; Okamoto, Y.; Takamuku, S. (Phosphorus, Sulfur Silicon Relat. Elem., 1991)

(untitled) - Nakamura, M.; Sawasaki, K.; Okamoto, Y.; Takamuku, S. (Bull. Chem. Soc. Jpn., 1995)

(untitled) - Nakamura, M.; Okamoto, Y.; Takamuku, S. (Phosphorus, Sulfur Silicon Relat. Elem., 1995)

(untitled) - Okamoto, Y.; Tatsuno, T.; Takamuku, S. (Heteroat. Chem., 1996)

(untitled) - Genkina, G. K.; Shipov, A. E.; Mastryukova, T. A.; Kabachnik, M. I. (Russ. J. Gen. Chem., 1996)

(untitled) - Bruice, T. C.; Blaskó, A.; Petyak, M. E. (J. Am. Chem. Soc., 1995)

(untitled) - Dichiarante, V.; Dondi, D.; Protti, S.; Fagnoni, M.; Albini, A. (J. Am. Chem. Soc., 2007)

(untitled) - Protti, S.; Fagnoni, M. (Chem. Commun., 2008)

(untitled) - Chen, X.; Chen, Z.; So, C. M. (J. Org. Chem., 2019)

(untitled) - Chen, Z.; Chen, X.; So, C. M. (J. Org. Chem., 2019)

CRC Handbook of Organic Photochemistry and Photobiology - Ravelli, D.; Fagnoni, M. (Photochemistry of Phosphate and Sulfonate Esters, 2012)

(untitled) - Cornelisse, J.; Havinga, E. (Chem. Rev., 1975)

(untitled) - Chopa, A. B.; Silbestri, G. F.; Lockhart, M. T. (J. Organomet. Chem., 2005)

(untitled) - Naito, I.; Kinoshita, A.; Okamoto, Y.; Takamuku, S. (ACS Symp. Ser., 1995)

(untitled) - Siqintuya; Sueishi, Y.; Yamamoto, S. (J. Photochem. Photobiol., A, 2007)